Progress and Working Hours: A Comparison of the Views of Marx, Keynes and Social Democracy - Schütz, Bernhard (Momentum Quarterly, 2014)
The ideas of Karl Marx and John Maynard Keynes had a great influence on Austrian social democracy. Both authors considered human self-realization the ultimate goal of history. Moreover, both thought that a sub- stantial reduction in working hours would be a prerequisite for achieving this purpose. The paper asks whether this specific idea of progress can also be found in Austrian social democratic platforms.
Keywords: progress; Marx; Keynes; Social Democracy; reduction of working hours